Management of a fractured endodontically treated tooth with crown lengthening and glass fibre post: A case report - Kazi Hossain Mahmud; Fathimath Maaisha (Update Dental College, 2021)
Purpose: This clinical case discusses the step-by-step implementation of a core and a post system that uses a single resin composite material for cementation of a glass fibre post and core build up of a fracture endodontically treated maxillary left first premolar with gingivectomy as a crown lengthening procedure. Clinical considerations: Several materials and methods has been discussed in the literatures regarding restoration of endodontically treated teeth with minimal tooth structure left which require fibre post and core build up. Gingivectomy as a crown lengthening is also a common procedure that facilitates restorative dentistry. This case presents a restoration of a tooth with a short clinical crown by gingivectomy and post core build up by glass fibre post with a mono-block technique or core-and-post technique with dual cure composite resin as a luting and core build up material. Conclusion:Post and core is needed to restored tooth with little tooth structure remaining.Glass fibre post are prefabricated posts which makes it easy to manipulate and reduces chairs side time among other advantages. Use of single material system for post-and-core reduces the steps of manipulation and chair side time compared to conventional techniques. Clinical significance: More measures are required when different materials are used for post-cementation and core build-up, increasing the chair time and the number of interfaces between the materials. However, these shortcomings can be overcome by the mono-block technique where only one material is used for both cementation and core build up. Update Dent. Coll. j: 2021; 11(2): 38-42